2021
DOI: 10.1108/ijaim-07-2021-0155
|View full text |Cite
|
Sign up to set email alerts
|

Does XBRL help improve data processing efficiency?

Abstract: Purpose The US Securities and Exchange Commission (SEC) requires public companies to file structured data in eXtensible Business Reporting Language (XBRL). One of the key arguments behind the XBRL mandate is that the technical standard can help improve processing efficiency for data aggregators. This paper aims to empirically test the data processing efficiency hypothesis. Design/methodology/approach To test the data processing efficiency hypothesis, the authors adopt a two-sample research design by using da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The sole purpose of using XBRL for financial reporting is to enhance the quality of publicly disseminated financial and non-financial information to various stakeholders (Zhou, 2019). Further, in other studies by Zhou (2019) and Rao and Guo (2022), it is noted that the prime concern behind the development and implementation of XBRL technology for financial reporting was to ensure transparency, reliability, accuracy, comparability and efficiency of annual financial reports communicated to end-users. In addition, there were studies (Valentinetti and Rea, 2011;Bovee et al, 2002 andTawiah andBorgi, 2022) that stressed that another important concern behind the adoption of XBRL technology for financial reporting was to eliminate the diversity and bring uniformity in financial reports of various companies in a capital market.…”
Section: Influence Of Xbrl Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…The sole purpose of using XBRL for financial reporting is to enhance the quality of publicly disseminated financial and non-financial information to various stakeholders (Zhou, 2019). Further, in other studies by Zhou (2019) and Rao and Guo (2022), it is noted that the prime concern behind the development and implementation of XBRL technology for financial reporting was to ensure transparency, reliability, accuracy, comparability and efficiency of annual financial reports communicated to end-users. In addition, there were studies (Valentinetti and Rea, 2011;Bovee et al, 2002 andTawiah andBorgi, 2022) that stressed that another important concern behind the adoption of XBRL technology for financial reporting was to eliminate the diversity and bring uniformity in financial reports of various companies in a capital market.…”
Section: Influence Of Xbrl Technologymentioning
confidence: 99%
“…However, a study by Bartolacci et al (2021) revealed that there is a scarcity of studies focused on the consequences of the adoption of XBRL for financial reporting. In addition, Rao and Guo (2022) also opined that there is a need to empirically assess the expected benefits of XBRL in improving the quality of business reporting.…”
Section: Influence Of Xbrl Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…It was revealed that there are significant differences in terms of shared information among different companies. Data processing efficiency in financial reports was calculated by Rao and Guo [3] in their work. Therefore, they compared the EDGAR and COMPUSTAT databases.…”
Section: Introductionmentioning
confidence: 99%